Heavy Burdens of Family Caregivers Caring for Persons with Severe Mental Disorders - Kissa Bahari; Arief Bachtiar; Gracia Herni Pertiwi; Ahmad Syahlani (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
Family caregivers who live with and care for individuals with severe mental disorders face serious issues. This study aimed to investigate the burdens of these family caregivers. This descriptive phenomenological study involved 15 family caregivers who looked after persons with mental disorders in Malang City, Indonesia; the participants were selected using a purposive sampling technique. Data were gathered using individual in-depth interviews and observations, and then analyzed inductively. Based on the findings, the burdens of family caregivers can be grouped into four main themes: 1) families encountered challenges and stigma in caring for persons with severe mental disorders, 2) there was a lack of support from the community and healthcare providers, 3) family caregivers reported experiencing various negative emotions and interpreting negative implications from their caregiving experiences, and 4) family caregivers employed coping strategies to alleviate their burdens. The researchers conclude that family caregivers experience complex burdens when caring for persons with severe mental disorders; hence, family caregivers need the support of healthcare personnel and community presence in situations of caring for persons with chronic mental disorders. Keywords: burden of disease, caregiver, family, Indonesia, severe mental disorders Abstrak Beban Berat Caregiver Keluarga dalam Merawat Orang dengan Gangguan Jiwa Berat. Caregiver keluarga yang hidup bersama orang dengan gangguan jiwa berat menghadapi masalah yang serius. Penelitian ini bertujuan untuk mengetahui secara mendalam beban para caregiver keluarga. Penelitian fenomenologi deskriptif ini melibatkan 15 caregiver keluarga yang merawat orang dengan gangguan jiwa di Kota Malang, Indonesia; partisipan dipilih dengan teknik purposive sampling. Pengumpulan data menggunakan metode wawancara mendalam secara individual dan observasi, serta selanjutnya dianalisis secara induktif. Hasil penelitian menunjukkan bahwa beban caregiver keluarga dapat dikelompokkan ke dalam empat tema utama: 1) keluarga menghadapi tantangan dan stigma dalam merawat orang dengan gangguan jiwa berat, 2) kurangnya dukungan masyarakat dan penyedia layanan kesehatan keluarga, 3) caregiver keluarga mengalami berbagai perasaan negatif dan memaknai secara negatif pengalamannya, dan 4) caregiver keluarga menggunakan strategi koping untuk meringankan beban keluarga. Peneliti menyimpulkan bahwa caregiver keluarga mengalami beban yang kompleks saat merawat orang dengan gangguan jiwa berat; oleh karena itu, caregiver keluarga sangat membutuhkan dukungan dari tenaga kesehatan dan kehadiran masyarakat sekitar dalam menghadapi situasi perawatan kronis bagi orang-orang dengan gangguan jiwa berat. Kata Kunci: beban penyakit, caregiver, gangguan jiwa berat, Indonesia, keluarga